The Voice Is the Message: emotional Practices and Court Rhetoric in Early Twentieth Century Germany - Schnädelbach, Sandra (Oñati Socio-Legal Series, 2019)
This paper illustrates that emotions were considered a central component of juristic work in German legal thought around 1900, showing how emotional practices of judges were reshaped when they were confronted with new socio-political demands in the early 20th century. It argues that judicial emotions were intensely reflected upon and used by German jurists, especially via court rhetoric and specific politics of voice. It puts forward an understanding of vocal performances as emotional practices that became particularly contested during the first decades of the 20th century. Whereas classical ideals of judicial conduct placed a premium on authority and distance in order to ensure objectivity, a psychologically informed and emotion-based interaction between judges and court attendees came to the fore: the use of rhetoric and the ability of showing, forming, and creating emotions gained relevance. The judge was not only to manage his own emotions, but was conceived of as an active engineer of emotions in court.